Bacteriophage Lambda Genomic Library Construction of Oryza sativa L. var. Pokkali - Rahman, Suhaila; Ohto, Masa-aki; Seraj, Zeba I.; Blumwald, Eduardo (Plant Tissue Culture and Biotechnology, 2009)
A major QTL called ‘Saltol’ on rice chromosome 1 has been identified as linked to salinity tolerance traits of the landrace, Pokkali. A genomic library of Pokkali rice variety was constructed in bacteriophage Lamda Fix II with 20 kb inserts. Plaques containing genes implicated to salt tolerance have been identified using probes homologous to S-Ad methionine synthetase (SAM) and cation chloride co-transporter after two rounds of hybridization. Clearly demarcated plaques of the two clones of interest have been lifted out for DNA isolation and subsequent characterization to be followed by subcloning into TAC vectors for Agrobacterium-mediated transformation of large genomic fragments into sensitive rice. Key words: Rice, Pokkali, Genomic library, Lambda vector, Partial Fill-In, Titer D.O.I. 10.3329/ptcb.v17i2.3235 Plant Tissue Cult. & Biotech. 17(2): 149-159, 2007 (December)